Institutions, the common agricultural policy, and the European Community's enlargement to Spain, 1977-1986 - Ruano, L (2001)
﻿ Why did EC enlargement negotiations with Spain take so long? This thesis argues that agricultural issues dominated negotiations despite the political and strategic aims of stabilizing Western Europe's southern flank that underpinned the raison d'être of this enlargement. The framework of Historical New Institutionalism is used to argue that several 'biases' operating at three levels account for the length and nature of these negotiations. At the first level, the 'bilateral' format of the negotiation procedure between Spain and the EC favoured existing EC members and protected the acquis communautaire. The Community's negotiating positions, as bargains in themselves, tended to be inflexible, and reduced Spain's input in the discussions and in the agenda-setting process. At the EC level, the CAP exhibited an unusual capacity to withstand the changes required by enlargement. This was because the EC's decisionmaking structure was fragmented into sectors and levels which allowed a closely knit 'policy community' to run the CAP in a way that was relatively insulated from other issue-areas. Change in the CAP occurred to cope with enlargement, but in a path-dependent way, passing the cost of adaptation on to Spain. At the national level, member states' so-called national interests with regard to enlargement were mixed, with no clear priority, and conflicting sectoral views. This resulted from the mechanisms of interest intermediation and inter-departmental co-ordination, which shaped the formulation and representation of national views in Brussels. Spain's accession was finally made possible when new redistributive policies for the Mediterranean and fresh budgetary resources were agreed. These were approved as part the wider package-deals surrounding the Single Market project and the Single European Act. HNI provides a new and persuasive framework with which to understand the difficulties of institutional change associated with enlargement negotiations.